Roll roofing with combination of MDF board - Mohd Khairy, Syazwani Aqilah (2022)
Malaysia is a growing third-world country that is still experiencing fast economic growth. The construction industry is one of Malaysia's most active industries, contributing significantly to the country's economic growth. Construction industry had gone through several changes starting from ancient methods to conventional and now moving towards to technology. The Industrial Building System (IBS) is gaining popularity in the building sector due to its numerous benefits. The roof is the most significant part of the building since it protects the occupants from a variety of hazards. Roofing needs have increased across the board, resulting in a robust market for roofing materials in terms of performance and physical properties. However, there are several issues that affect the efficiency of the roof materials. According to past research, there have been various challenges affecting the effectiveness of roofing materials. The main identified issues are cracked concrete roof tiles, water absorption and heavyweight. It gives an opportunity to suggest new innovation products to tackle significant concerns by identifying problems. As a result, new innovative concepts are presented to address the highlighted concerns while also promoting the use of construction waste materials for roofing, that is roll roofing with combination of MDF board.